Synthesis, cytotoxic, anti-lipoxygenase and anti-acetylcholinesterase capacities of novel derivatives from harmine. (1st November 2016) - Filali, Insaf; Belkacem, Mohamed Amine; Ben Nejma, Aymen; Souchard, Jean Pierre; Ben Jannet, Hichem; Bouajila, Jalloul
Abstract: We synthesized two series of new hydrazide harmine derivatives. The reaction of harmine1 with ethyl acetate chloride afforded the corresponding ethyl ester2 . The treatment of2 with hydrazine hydrate gave the hydrazide3 which further converted into hydrazones4a –j and dihydrazides5a –c . A series of new triazoles7a –f has also been prepared from the suitable propargyl harmine6 . The synthesized derivatives were characterized by 1 H-NMR, 13 C-NMR, and HRMS and evaluated for their activities against MCF7, HCT116 OVCAR-3, acetylcholinesterase and 5-lipoxygenase. The most hydrazones derivatives4a-j have a good cytotoxic activity against all cell lines, when4a, 4d, 4f and4 g are more active than1 (against OVCAR-3 IC50 16.7–2.5 μM). The compound6 was the most active (IC50  =  1.9 μM) against acetylcholinesterase. Some compounds exhibited significant activity against 5-lipoxygenase (IC50  =  30.9–63.1 μM).